Analisis Tongkonan Performance Terhadap Minat Kunjungan Wisatawan di Tana Toraja - Whindy Randa; Abdullah Abdullah; Jumaidah Jumaidah (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine whether the performance of Tongkonan has an impact on tourists' interest in revisiting Tana Toraja. The population of this study was all visitors who visited Tana Toraja. While the sampling method used is to use the slovin method so that the number of samples obtained is 399 people. By using data collection methods using questionnaires and observations. While the analysis method used is quantitative descriptive analysis.